(3GdOQQ GdeaGNQ aj CNHGQ GdYQH GdChGNQs
(3ChdgG (B:s
(3GdMeO ddg GdeJaQO HEjLGO GdCfhGY GdeJhMO HGdEfTGA hGdENJQGY hHYO abO gR eYGWai hCeGd gPGA ShGdai HYV GdCUObGA ef Chdi GdCOH dVe Ted GdeJBNQjf ef bHGFd GdYQH s
(3BNQgG (B:s
(3hGdQGHY HbHGFd fLO hGdNGeS HPcQ YeGf hGdSGOS HCNHGQ GdEMSGA hGdSGHY ai bHGFd GdYQGbi hGdKGef ai bHGFd MdH hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs